The economics of crime and punishment - Rottenberg, Simon; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1973)
This volume comprise of papers presented at a conference held July 1972 in Washington, D.C on the economics of crime and punishment.
A Conference sponsored by American Enterprise Institute for Public Policy Research.
Includes bibliographical references.
lje 25/01/2019
Loans
Keywords: Crime; Punishment; Organized crime; Criminal procedure